Variability Assessment of Aromatic and Fine Rice Germplasm in Bangladesh Based on Quantitative Traits - M. Z. Islam; M. Khalequzzaman; M. K. Bashar; N. A. Ivy; M. M. Haque; M. A. K. Mian (The Scientific World Journal)
The study was conducted to investigate genetic variability among 113 aromatic and fine local rice genotypes of which five were exotic in origin. The test genotypes were evaluated for 19 growth traits, yield components, and yield. All the quantitative traits varied significantly among the test genotypes. High heritability along with high genetic advance was observed for flag leaf area, secondary branches per panicle, filled grains per panicle, grain length, grain breadth, grain length breadth ratio, and 1000 grain weight. Such findings suggested preponderance of additive gene action in gene expression for these characters. Grain yield was significantly and positively correlated with days to flowering, days to maturity, panicle length, filled grains per panicle, and 1000 grain weight. According to D2 cluster analysis, 113 test genotypes formed 10 clusters. Selection of parents from the clusters V and X followed by hybridization would possibly result in desirable heterosis for the development of heterotic rice hybrids. Finally, molecular characterizations of the studied germplasm are required for high resolution QTL mapping and validating the presence of candidate genes responsible for valuable characters.